2016
DOI: 10.1016/j.sjbs.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value and proteases of Lentinus citrinus produced by solid state fermentation of lignocellulosic waste from tropical region

Abstract: This paper examined the growth and yield performance of Lentinus citrinus on cupuaçu exocarp (Theobroma grandiflorum) mixed with litter (CE + LI) or rice bran (Oryza sativa) (CE + RB) in the ratio of 2:1 (800 g:200 g) to investigate the nutritional composition and proteolytic potential of the fruiting body produced. Significance values of yield were determined on substrate combinations. In CE + LI the biological efficiency of the mushrooms was 93.5% and the content of fat (4.5%), fiber (11.0%), protein (27.0%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 20 publications
5
26
0
5
Order By: Relevance
“…Glutamic acid has an important role as brain stimulatory neurotransmitters and enhancing food flavor (Fonseca et al, 2015). Machado et al (2015) observed amino acids values close to those presented in this study.…”
Section: Mineral Contentsupporting
confidence: 90%
See 2 more Smart Citations
“…Glutamic acid has an important role as brain stimulatory neurotransmitters and enhancing food flavor (Fonseca et al, 2015). Machado et al (2015) observed amino acids values close to those presented in this study.…”
Section: Mineral Contentsupporting
confidence: 90%
“…Among the micronutrients, manganese content was higher, followed by iron, zinc and copper. Machado et al (2015) had good values of potassium, phosphorus, iron, zinc and copper as in this study. Lee et al (2009) and Medina et al (2009) also observed increase in the concentration of minerals in the substrates after cultivation.…”
Section: Mineral Contentsupporting
confidence: 70%
See 1 more Smart Citation
“…The results of this study with P. ostreatoroseus were higher than the ones reported by Fonseca et al (2014), who observed significant proteolytic activity (7.89 U/mL) from P. ostreatoroseus using cupuaçu exocarp supplemented with 20% rice bran as substrate. Similar results were reported by Machado et al (2016) and Souza et al (2016) that cultivated L. citrinus on cupuaçu exocarp supplemented with litter and pineapple bark without supplementation, respectively. The results of this investigation revealed that the use of the tubers, especially D. alata, as substrates promoted the production of proteases by P. ostreatoroseus and L. citrinus.…”
Section: Proteolytic Activitysupporting
confidence: 90%
“…At high temperatures, the enzymes suffer protein denaturation because the intramolecular bonds are affected (Ahmed et al, 2011). In the studies of Fonseca et al (2014), Guan et al (2011) and Machado et al (2016), the optimum temperature activity of the mushrooms P. ostreatoroseus, Pholiota nameko and L. citrinus was also determined at 40 and 50°C, respectively. The stability of pH and temperature is an important parameter in the enzymes application due to their determination of economic availability in the industrial processes (Moretti et al, 2012).…”
Section: Effect Of Ph and Temperature On Enzyme Activity And Stabilitymentioning
confidence: 99%